Limit theorems for multi-type general branching processes with population dependence. (December 2020) - Fan, Jie Yen; Hamza, Kais; Jagers, Peter; Klebaner, Fima C.
Abstract: A general multi-type population model is considered, where individuals live and reproduce according to their age and type, but also under the influence of the size and composition of the entire population. We describe the dynamics of the population as a measure-valued process and obtain its asymptotics as the population grows with the environmental carrying capacity. Thus, a deterministic approximation is given, in the form of a law of large numbers, as well as a central limit theorem. This general framework is then adapted to model sexual reproduction, with a special section on serial monogamic mating systems.